Integrating Pathways of Parkinson's Disease in a Molecular Interaction Map - Fujita, Kazuhiro A. (Springer US, 2013)
Parkinson's disease (PD) is a major neurodegenerative chronic disease, most likely caused by a complex interplay of genetic and environmental factors. Information on various aspects of PD pathogenesis is rapidly increasing and needs to be efficiently organized, so that the resulting data is available for exploration and analysis. Here we introduce a computationally tractable, comprehensive molecular interaction map of PD. This map integrates pathways implicated in PD pathogenesis such as synaptic and mitochondrial dysfunction, impaired protein degradation, alpha-synuclein pathobiology and neuroinflammation. We also present bioinformatics tools for the analysis, enrichment and annotation of the map, allowing the research community to open new avenues in PD research. The PD map is accessible at http://minerva.uni.lu/pd_map. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12035-013-8489-4) contains supplementary material, which is available to authorized users.